Missense mutations in small muscle protein X-linked (SMPX) cause distal myopathy with protein inclusions - Johari Mridul; Sarparanta Jaakko; Vihola Anna; Jonson Per Harald; Savarese Marco; Jokela Manu; Torella Annalaura; Piluso Giulio; Said Edith; Vella Nrbert; Cauchi Marija; Magot Armelle; et al. (SPRINGER, 2022)
Using deep phenotyping and high-throughput sequencing, we have identified a novel type of distal myopathy caused by mutations in the Small muscle protein X-linked (SMPX) gene. Four different missense mutations were identified in ten patients from nine families in five different countries, suggesting that this disease could be prevalent in other populations as well. Haplotype analysis of patients with similar ancestry revealed two different founder mutations in Southern Europe and France, indicating that the prevalence in these populations may be higher. In our study all patients presented with highly similar clinical features: adult-onset, usually distal more than proximal limb muscle weakness, slowly progressing over decades with preserved walking. Lower limb muscle imaging showed a characteristic pattern of muscle involvement and fatty degeneration. Histopathological and electron microscopic analysis of patient muscle biopsies revealed myopathic findings with rimmed vacuoles and the presence of sarcoplasmic inclusions, some with amyloid-like characteristics. In silico predictions and subsequent cell culture studies showed that the missense mutations increase aggregation propensity of the SMPX protein. In cell culture studies, overexpressed SMPX localized to stress granules and slowed down their clearance.